Confirmation that Helopeltis species attacking cacao in Yogyakarta is Helopeltis bradyi Waterhouse, not Helopeltis antonii Signoret (Heteroptera: Miridae) - Susi Melina; Edhi Martono; Y. Andi Trisyono (Jurnal Entomologi Indonesia, 2016)
Helopeltis antonii Signort (Heteroptera: Miridae) has long been reported to attack cacao and other host plants in Java. A recently published literature review refuted this idea and offered morphological evidence suggesting that this attacker is actually H. bradyi Waterhouse. However, through the present, local reports still identify attacks as coming from H. antonii. To confirm which of these two species is implicated in cacao damage, we conducted an examination of the external morphology, genitalia and the biology of Helopeltis sampled from infested cacao plants in Yogyakarta. 42 females and 9 males, sampled from 3 different locations, were observed to be morphologically similar to H. bradyi, especially with regard to the pale band on the base of all femora, the knife-shaped male lobal sclerite, and the presence of a ‘Y’ shaped junction on the posteriorly fused female genital chamber. The duration of the life stages (in days) of the laboratory-reared insects were: 7−11 (eggs), 12−19 (nymphs), 9−44 (female) and 16−54 (male) d, measurements which fall within the ranges of the parameters usually reported locally for H. antonii, with the exception of male adult life stages which are longer than the aforementioned reports. Morphological changes were observed during all stages of development, including within adult stages. In female adults specifically, external morphology and genital development proceeded continuously until the insects reached the full-grown condition, characterized by stable color, and fully sclerotized genital chamber. Our preliminary study of the morphology and development of lab-reared insects descended from individuals infesting cacao fields, indicated the presence of H. bradyi instead of H. antonii in Yogyakarta, and therefore stipulated a need to review the existence of the latter in Indonesia.